1985
DOI: 10.1007/bf00391273
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels in Eremosphaera viridis

Abstract: The dependence of the membrane potential of Eremosphaera viridis on different external concentrations of potassium, sodium, calcium, and protons was compared with the diffusion potential measured in the dark and in the presence of NaN3. In contrast to some other algae, the membrane potential in the light as well as in the dark seemed to be predominantly determined by the calculated diffusion potential and less by an electrogenic pump which, however, seemed to be involved at potassium concentrations >1 mol·m(-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The course of these transient currents could be subdivided into three phases: a fast activation phase, a short plateau phase and a slow inactivation phase. This corresponds to the course of transient potassium currents measured by Kohler et al (1986) in intact cells of Eremosphaera. Hence, we assume these inward currents to be caused by the activity of potassium channels responsible for the TP in this alga.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The course of these transient currents could be subdivided into three phases: a fast activation phase, a short plateau phase and a slow inactivation phase. This corresponds to the course of transient potassium currents measured by Kohler et al (1986) in intact cells of Eremosphaera. Hence, we assume these inward currents to be caused by the activity of potassium channels responsible for the TP in this alga.…”
Section: Resultssupporting
confidence: 58%
“…the socalled transient potential (TP). The properties of this TP have already been characterized by means of conventional electrophysiological methods (for summary see Kohler. 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Some cell-wide binary responses mediated by action potentials have been described in other protists—for example, the escape response of Stentor , Vorticella and Actinocoryne ( box 2 )—but they involve highly specialized mechanisms and are probably derived. Action potentials of unknown function have also been detected in the green algae Chara [ 173 ], Eremosphaera [ 174 , 175 ] and Acetabularia [ 51 ], and in the diatom Odontella [ 176 ].…”
Section: The Ciliary Origin Of Action Potentialsmentioning
confidence: 99%
“…This paper deals with a particular aspect of such a feed-back loop: the activation and deactivation ofthe transport molecule. The basic ideas of this approach are not restricted to homeostasis, because activation and deactivation of transport molecules becomes obvious in phenomena like excitation (Kohler et al, 1986), oscillations (Fisahn et al, 1986) or switching between open and closed states of channels as observed in patch clamp experiments (Sakmann and Neher, 1983;Bert1 et al, 1988).…”
Section: Introductionmentioning
confidence: 99%